Composition, determinants, and risk factors of low birth weight in Sri Lanka. - Sachith Mettananda; Himali Herath; Ayesha Thewage; Kumudu Nanayakkara; Indeewari Liyanage; K S Udani; Rajika Savanadasa; Sampatha Goonewardena; Nimesha Gamhewage; Asiri Hewamalage; Dhammica Rowel; Abner Elkan Daniel; et al. (PLoS ONE)
Introduction Low birth weight continues to pose significant challenges to healthcare systems worldwide. Despite substantial improvement in various public health indicators, many developing countries have failed to achieve a significant reduction in low birth weight rates. One major obstacle is the sparsity of data on the determinants of low birth weight. Here, we aim to determine the composition and risk factors for low birth weight in Sri Lanka, a prototype developing nation. Methodology We conducted a countrywide multicentre cross-sectional study in August and September 2023 in 13 purposively selected hospitals representing all nine provinces and different tiers of specialist hospitals in Sri Lanka. All live-born neonates were recruited prospectively, and their mothers were interviewed by trained data collectors to gather information on socio-demographic background, medical and obstetric history, and delivery details. Birth weight was measured immediately after the birth by trained healthcare personnel attending the delivery. Results A total of 9130 live-born neonates were recruited, of which 52% were males. The mean birth weight was 2827g (95%CI 2817-2838g), and 1865 (20.4%) newborns were low birth weight. The prevalence of prematurity was 10.9% (n = 998), and 1819 (20.0%) neonates were born small for gestational age. Of the low birth weight neonates, 64% were small for gestational age, and 37% were preterm; 11% were both small for gestational age and preterm. Teenage pregnancy (p = 0.022), low maternal pre-pregnancy body mass index (p<0.001), inadequate weight gain during pregnancy (p<0.001), maternal anaemia at delivery (p = 0.020), chronic lung disease (p = 0.019), and pregnancy induced hypertension (p = 0.019) were significant modifiable risk factors for small for gestational age. Conclusion This study presents the results of one of the most extensive country-wide studies evaluating the composition and determinants of low birth weight. The study highlights the importance of considering small for gestational age and prematurity as separate categories of low birth weight. Small for gestational age contributes to approximately two-thirds of the low birth weight burden. Therefore, targeting modifiable risk factors for small for gestational age while mitigating the burden of prematurity is the most feasible approach to reduce the prevalence of low birth weight in developing countries, including Sri Lanka.